2011
DOI: 10.21608/jappmu.2011.83362
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of New Nutritional Resources in Ruminant Feeding: 2) Effect of Using Dried Distillers Grains With Soluble (Ddgs) as Protein Source in Rations for Fattening Buffalo Calves

Abstract: The present work was carried out to study the effect of using dried distillers grains with soluble (DDGS) as a source of protein in ration formulation of buffalo calves. DDGS was included in concentrate feed mixture (CFM) at 0, 11, 16, 21 and 27% to cover 0, 20, 30, 40 and 50% of total protein, respectively. Fifty male buffalo calves averaging 320.16 kg live body weight were randomly distributed into five similar groups (10 in each) and assigned to receive five concentrate feed mixtures containing five levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…Table (5) showed that the average daily feed unite intakes increased with increasing guar korma percentages in CFM owing due to its high palatability and higher both digestibility and feeding values of guar korma. Such results were agreement with those reported by Etman et al, 2011 and2014;Turki et al, 2011;Shwerab et al, 2010 andSehgal andMakker, 1994. Effect of feeding guar korma on blood parameters:…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Table (5) showed that the average daily feed unite intakes increased with increasing guar korma percentages in CFM owing due to its high palatability and higher both digestibility and feeding values of guar korma. Such results were agreement with those reported by Etman et al, 2011 and2014;Turki et al, 2011;Shwerab et al, 2010 andSehgal andMakker, 1994. Effect of feeding guar korma on blood parameters:…”
Section: Resultssupporting
confidence: 93%
“…Also, there were improvements in economical efficiency with increasing guar korma level in experimental rations, being 3.52, 8.23, 13.29, 19.21 and 23.76% with rations B, C, D, E and F, respectively. From the previous results, it may be shown that the animals fed rations containing the highest level of guar korma (16.7%) which represent 50% as a source of protein of CFM appeared to have the lowest feed cost/kg gain with the highest revenue, profit and economical efficiency. The results were agreement with those reported by Turki et al, (2011), Saleh pour et al(2012),TarunaKhanna et al, (2010 and Etman et al, (2011 and2014) CONCLUSION Guar korma meal could be used as a source of protein to partially or totally replace cotton seed cake and soybean meal in concentrate feed mixture of growing buffalo calves rations. Moreover, guar korma meal could be used at the rate of 50% in CFM instead of both cotton seed cake and soybean meal in ration formulation of buffalo calves.…”
Section: Feed Cost and Economical Efficiencysupporting
confidence: 92%
“…In addition, Shwerab et al (2010) showed higher digestibility coefficients and nutritive value with increasing DDGS in sheep rations. The same results were obtained with Etman et al (2011). They found that using DDGS as a source of protein in rations formulation of buffalo calves increased digestibility coefficients of all nutrients and feeding values.…”
Section: Nutrient Digestibility and Feeding Valuessupporting
confidence: 75%
“…The obtained values of some blood profiles of tested groups in present study were within the normal range for healthy goats given by Plumb (1999) being 2.4:4.4 g/dl , 64.6:136.4 mg/dl , 0.9:1.8 mg/dl , 66:230 and 15.3:52.3 U/L for albumin , cholesterol , creatinine , AST and ALT concentrations , respectively. However Etman et al (2011) recorded that most of blood parameters were not affected by adding DDGS in experimental rations with fattening buffalo calves. tested rations.…”
Section: Blood Constituentsmentioning
confidence: 95%
“…Similar results reported by Gabr et al (2010a) , Ghoneem and Mahmoud (2016) and Etman et al(2012). In general, liver function might be affected by other factors such as age, body weight or administrative circumstance related to good or bad feeding (Etman et al, 2011).…”
Section: Blood Constituentsmentioning
confidence: 99%